The zest for migration and national development in Nigeria - Okafor, Frank-Collins Nnamdi (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2012)
The problem created by the mass movement of Nigerian youth outside the country in search of greener pastures cannot be overemphasized. More worrisome,however, are the losses suffered by the country because of the unbridled zest for migration held by those still within the country who hope that one day they will also migrate. This paper takes a critical look at the situation with special attention to what engineers this zest in young Nigerians, as well as the special problems it creates. It concludes that the Nigerian nation loses a great deal in terms of the contributions that might be made to the development of the state by those young people who wait hopelessly and helplessly for the day their dreams may materialize. It also offers the best ways out of these direstraits for the Nigerian state and other states in this kind of situation.
Keywords: Nigeria; Nigerija; human migration; migracije; nacionalni razvoj; nakazila migrantov